2014
DOI: 10.1017/s0030605313000276
|View full text |Cite
|
Sign up to set email alerts
|

A frame-analytical perspective on conflict between people and an expanding wolf Canis lupus population in central Italy

Abstract: Attempts to mitigate conflict between wolves and livestock breeding in the Mugello area of central Italy have so far proven to be costly, resource-intensive and fraught with tension. I applied frame analysis as a tool for investigating the roots of such tensions. The frameanalytical perspective highlighted that, while current policy focuses on improving technical approaches, conflict is also fuelled by a discrepancy in the frames of meaning that groups of stakeholders construct around the issue of wolf managem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…More than 80 % of the farmers distrusted the official numbers of carnivore numbers, suspecting them of being too low and manipulated by the environmental authorities. In a frame analysis in Italy, Vitali (2014) reported that the perspectives of administrators and policy-makers, on the intrinsic value of the wolf, permeated the dominating frame, while the competing frame, confined largely to rural respondents, claimed that human activities should be the first priority within conservation policy. It has been suggested that the relationship between Scandinavians who live in large-carnivore areas and the managing authorities may be inflated by diverging values related to protection of nature corresponding to a utilitarian/ mutualist divide or a more anthropocentric vs ecocentric or biocentric view on nature Heberlein 2003a, 2003b;Skogen and Krange 2003;Skogen and Thrane 2007;Skogen et al 2008;Blekesaune and Rønningen 2010).…”
Section: Geographical Location and Standpoint On Protected Naturementioning
confidence: 99%
“…More than 80 % of the farmers distrusted the official numbers of carnivore numbers, suspecting them of being too low and manipulated by the environmental authorities. In a frame analysis in Italy, Vitali (2014) reported that the perspectives of administrators and policy-makers, on the intrinsic value of the wolf, permeated the dominating frame, while the competing frame, confined largely to rural respondents, claimed that human activities should be the first priority within conservation policy. It has been suggested that the relationship between Scandinavians who live in large-carnivore areas and the managing authorities may be inflated by diverging values related to protection of nature corresponding to a utilitarian/ mutualist divide or a more anthropocentric vs ecocentric or biocentric view on nature Heberlein 2003a, 2003b;Skogen and Krange 2003;Skogen and Thrane 2007;Skogen et al 2008;Blekesaune and Rønningen 2010).…”
Section: Geographical Location and Standpoint On Protected Naturementioning
confidence: 99%
“…Consequently, how policies and institutions are designed to guide governance and management is key to the future development of the wolf as a species. This fact emphasizes the need for an increased understanding of the interaction between social and ecological change, and public attitudes towards wolf policy, in order to develop policies and methods of wolf conservation that are perceived as legitimate [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the increasing number of wolves (Canis lupus) in central Italy (Bassi et al 2015b;Vitali 2014) has led to an increase in semi-extensive farming, with an increased use of fenced pastures and housing facilities, which promote the spread and concentration of environmental spores, especially when the bedding is not managed appropriately. In this regard, in some areas of Spain and France, a ewe's milk quality payment system has been adopted in order to promote farm management practices that are effective in reducing the clostridial spores load of the milk.…”
Section: Introductionmentioning
confidence: 99%